The Correlation between Students’ Vocabulary Mastery and Reading Comprehension - Alan Hubert Frederick Sanger; Alva Frisky Sanger (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This research aimed to investigate the levels of vocabulary, reading comprehension, and to examine whether there was a significant correlation between vocabulary mastery and reading comprehension among students. The research was quantitative in design, using descriptive and correlation methods. Purposive sampling technique was employed. The instruments used in the research were two adapted types of tests from Erniwati (2019) consisting of vocabulary mastery and reading comprehension. In the data analysis section, mean values and Pearson Correlation were used in the research. The population for the study were grade 8 of UNKLAB Junior High School which consisted of 136 students and total respondents were the 64 students. The result of the findings of vocabulary mastery level is 87 which categorized in understanding level, the level of reading comprehension is 74 which categorized in developing level, and the correlation between students’ vocabulary mastery and reading comprehension is 0.636 which classified there was a significant correlation between the two variables. The It could be concluded that when students have a larger vocabulary, they will comprehend the reading texts better.